DIGITAL EXCLUSION IN BRAZIL: ASSESSMENT AND INTERVENTIONS FOR A MORE CONNECTED SOCIETY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This article aims to conduct a study on the direct impact of societal development on the stratification of access to technological means in Brazil, as digital exclusion is a reflection of inequalities. This concept is associated with the hindrance preventing digitally excluded individuals from interacting with information. As a solution, digital inclusion measures are imperative, as they enable these citizens to acquire knowledge and develop intellectual capital, thus contributing to the social, cultural, and economic progress of the Brazilian community. At the same time, we will address the information gap between the wealthier and the less privileged groups. Using descriptive bibliographical research methods, we seek to outline the issue of digital exclusion and some of the potential impacts it can have on our society while presenting key strategies to resolve the problem.